Os pressupostos liberais e republicanos para articulação entre autonomia privada e soberania popular na filosofia política e jurídica no pensamento de Kant - Nascimento, Francisco Eliandro Souza do (2023)
The present work intends to carry out an analysis of the relationship between private autonomy and popular sovereignty in the philosophy of law and political philosophy of Immanuel Kant. Based on this analysis, we intend to support the hypothesis that the way in which Kant relates private autonomy and popular sovereignty are symmetrically articulated, as we consider that the principle of the sovereignty of the people is not restricted by private autonomy or private autonomy is suppressed in the face of the force of the general will, both principles are symmetrically articulated, one being a condition for the realization of the other. We also argue that the Kantian theory cannot be interpreted as a liberal or republican theory, since the two principles (private autonomy and popular sovereignty) are in a symmetrical and complementary relationship in the philosophy of law and in political philosophy. Kantian political philosophy unifies elements of the liberal paradigm and the republican paradigm to build the political project of a State that guarantees, on the one hand, the private autonomy of each citizen and, on the other hand, the general will as the supreme principle of democracy. Kant's political project extends from a national policy to an international policy.